2023
DOI: 10.1111/jpy.13401
|View full text |Cite
|
Sign up to set email alerts
|

Description of two new species of Nostoc (Nostocales, Cyanobacteria) from central Mexico, using morphological, ecological, and molecular attributes

Javier Carmona Jiménez,
Angela Caro Borrero,
Itzel Becerra‐Absalón
et al.

Abstract: The present study describes two new Nostoc species, N. montejanii and N. tlalocii, based on a polyphasic approach that combines morphological, ecological, and genetic characteristics. The five investigated populations, including those from newly collected material from central Mexico, were observed to possess morphological features characteristic of the Nostoc genus. Results showed that both new species are strictly associated with running water, and they show clear differences in their habitat preferences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…tlalocii (BV = 100%), while the Tambaque population (BV = 53) represents N . montejanii (Carmona-Jiménez et al, 2023 ). Interestingly, populations from San Rafael and San Miguel showed morphological characteristics similar to Nostoc , but the phylogenetic analysis indicated that these belong to the Compactonostoc genus.…”
Section: Resultsmentioning
confidence: 99%
“…tlalocii (BV = 100%), while the Tambaque population (BV = 53) represents N . montejanii (Carmona-Jiménez et al, 2023 ). Interestingly, populations from San Rafael and San Miguel showed morphological characteristics similar to Nostoc , but the phylogenetic analysis indicated that these belong to the Compactonostoc genus.…”
Section: Resultsmentioning
confidence: 99%
“…The transformation process was carried out using 100 µ L of the competent bacteria strain Escherichia coli (DH5a) (Promega). The transformed bacteria were inoculated (250 μ L) in Petri dishes with solid LB medium [ 37 ], ampicillin (0.1 mg/mL), X-Gal: 5-bromo-4-chloro-3-indolyl- β -D-galactopyranoside (0.04 mg/mL), and IPTG: isopropyl- β -D-1-thiogalactopyranoside (0.5 mM) [ 38 ]. The cultures were incubated at 37°C for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Negative clones (blue colonies without insert) were discarded. The presence of the insert was confirmed by PCR and electrophoresis [ 38 ]. The reaction master mix used was the following: milli-Q water, 10x PCR buffer, Cl 2 Mg (50 mM), deoxyribonucleotide triphosphate (50 μ M dNTP), and DNA polymerase (Ultratools DNA Polymerase: 1 unit/ μ L and Thermo Scientific DreamTaq DNA Polymerase: 20 and 500 units/ μ l).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation